Microhabitat and microclimate preferences of anuran species inhabiting restoration and adjacent forest of Cameron Highlands, Pahang Darul Makmur, Malaysia - Nadia Simon,; Marina Mohd. Top,; Mohd. Zaki Hamzah,; Nor Azwady Abdul Aziz,; Mohamad Azani Alias,; Mohd. Ridza Awang,; Zahari Ibrahim,; Ahmad Fadzil Abd. Majid,; Mohd. Syahrir Azrin Salleh,; Azhar Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The conversion of forests to agricultural farmland modifies lands into small patches, making amphibians more susceptible to external environmental changes. It is important to restore the forest ecosystem so that fauna species, especially anurans, could gradually recover and help create a balanced ecosystem in the restoration process. The aims of this study are to determine diversity, richness, and evenness of the anuran species, and to investigate the relationship of the anuran species with environmental variables of restoration areas and adjacent forests of Terla Forest Reserve (FR), Cameron Highlands, Pahang. The study recorded 14 species belonging to six families with higher species diversity, whereby the Shannon Wiener (H’) value in the adjacent forest (H’ = 1.71) was higher as compared to the restoration area (H’ = 0.77). The anuran species in the restoration area showed an adaptation to bare soil, herbs, and shrubs. Meanwhile, in the forest, forest litter was favoured by the anuran species. Species abundance demonstrated correlation towards microclimate. The adaption of two species to the restoration area showed that temperature had a significant and negative correlation with Duttaphrynus melanostictus; relative humidity was significant and positively correlated with Polypedates leucomystax; while relative humidity had a significant and negative correlation with Microhyla annectens, a forest specialist. A deeper understanding of environmental factors that affect the presence of anurans, especially in restoration areas, can facilitate forest management in evaluating the effectiveness of forest restoration in this region.